Projected Analysis of Fulfilling Pdam Clean Water Needs in Domestic Customers of Waginopo Village, Wangi-Wangi District, Wakatobi District - Jamiludin Jamiludin; Esti Wulandari; Hanie Teki Tjendani (Interdiciplinary Journal and Hummanity (INJURITY), 2024)
Clean water is a very vital need for society, to meet the needs for drinking water, bathing, cooking, washing and including industrial needs. The existence of clean water in an area is very important considering the very dynamic activities of society. In its implementation, the drinking water supply system in Waginopo Village has not been able to run smoothly. In fact, according to a temporary survey that has been carried out, PDAM water only flows once every 2 days, once a week and the maximum flow time is only 12 hours. The aim of this research is to calculate the amount of clean water needed for the service area of Waginopo Village, Wangi-Wangi District, Wakatobi Regency until 2033. In this research, not only numerical data will be collected, but also information about what the community desires regarding the performance of the clean water distribution system, so this research study approach uses a combination of quantitative and qualitative approaches. From the results of the analysis it can be said that the total water demand of PDAM Wakatobi Regency for the Waginopo Village service area in 2033 is 867,894 m3/year. Meanwhile, based on water demand in 2024, it is 592,737 m3/year. So the calculation results from 2024 to 2033 have increased.